Strategi Pemasaran Syariah Pada Produk Cicilan Emas Dalam Upaya Meningkatkan Jumlah Nasabah Bsi Kcp Banyuwangi Purwoharjo - Nuril Fitriatussoleha; Mira Ustanti; Nurul Inayah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study analyzes the marketing strategy of gold installment products based on murabahah contracts at BSI KCP Banyuwangi Purwoharjo using qualitative methods and the SWOT approach. This analysis aims to identify strengths, weaknesses, opportunities, and threats in an effort to improve marketing effectiveness and minimize the risk of making inappropriate decisions. The findings show that the main strengths of the product lie in compliance with sharia principles, transparency of contracts, and stability of gold investment. However, weaknesses such as low public literacy and limited accessibility remain a challenge. On the other hand, opportunities such as increased awareness of sharia products and new market segments such as high school and university students can be utilized to expand customer outreach. The recommended strategies include product development for young segments, increasing financial literacy through education, optimizing digital promotions, and collaboration with educational institutions. With this approach, BSI KCP Banyuwangi Purwoharjo can strengthen its position in the market, face gold price fluctuations, and compete with other financial institutions. This study concludes that a combination of strengths and opportunities-based strategies and mitigation of weaknesses and threats can be the key to successful marketing of sharia-based gold installment products.